EFFECT OF FUROSEMIDE AND TORASEMIDE ON HEART RATE VARIABILITY AND VENTRICULAR RHYTHM DISORDERS IN PATIENTS WITH CHRONIC HEART FAILURE COMPLICATING ISCHEMIC HEART DISEASE: COMPARATIVE NONRANDOMIZED STUDY - H. H. Shugushev; A. A. Gaeva (Рациональная фармакотерапия в кардиологии)
Aim. To study effect of diuretic therapy with furosemide and torasemide on heart rate variability (HRV) and frequency of ventriclar rhythm disorders in patients with chronic heart failure (CHF) complicating ischemic heart disease (IHD).Material and methods. Patients (n=107) with CHF III-IV functional class (NYHA) complicating IHD were examined. The first group of patients received furosemide, 20-60 mg QD (n=52), the second group received torasemide, 5-20 mg QD (n=55). Analysis of heart rhythm disorders and the basic HRV indicators was performed by ECG 10-minute recordings initially and after 10 days of therapy.Results. Decrease in time and spectral HRV parameters and increase in daily number of ventricular extrasystoles was found in furosemide treated patients. Improvement of HRV parameters and reduction of daily number of ventricular rhythm disorders was found torasemide treated patients.Conclusion. Torasemide therapy improves an autonomic regulation of heart rhythm and leads to the reduction of ventricular heart rhythm disorders in patients with CHF complicating IHD.